Approach of calcium oxalate calculus recurrence prevention in dogs Keywords - KUWAHARA, Yasuhito (JOURNAL OF JAPANESE ASSOCIATION OF VETERINARY NEPHROLOGY AND UROLOGY, 2023)
Based on the previous reports related to formation of calcium oxalate calculus, we propose 10preventive measures that could be effective in preventing recurrence, and 9 urine tests that couldbe useful in modifying preventive policies during treatment process, as follows; (1)urine specificgravity, (2)urinary calcium/creatinine (cre) ratio, (3)oxalic acid/cre ratio, (4)citric acid/cre ratio, (5)magnesium/cre ratio, (6)uric acid/cre ratio, (7)inorganic phosphoric acid/cre ratio, (8)urine pH and(9)urine culture and susceptibility test. Furthermore, in order for these tests to be properly carriedout and evaluated in general veterinary hospitals, practical test methods and subcontractors willbe introduced, and provisional target values for each urine test will be described. However, thevalidity of preventive measures, inspection items and target values shown in this paper has notbeen fully examined. It is hoped that many hospitals will adopt these efforts in the future, andbased on the results, proposals in this paper will be revised and elaborated to establish betterrecurrence prevention measures.